Diseño de un sistema de coordinación de protecciones eléctricas, para mejorar la confiabilidad del suministro de energía eléctrica en la Base Aérea Cotopaxi en el año 2017. Coordinación de protecciones eléctricas utilizando la aplicación OETB de excel - Acosta Gutiérrez, Segundo Hernán (2017)
Cotopaxi Air Base has an uncoordinated electric protection system. Consequently, it affects the reliability of the electrical system and there is the constant risk of unexpected power outages, as well as it can cause damages to the equipment and the collapse of network. The purpose of this study was to design a system of coordination of electrical protections by using an OETB application in Excel, in order to improve the reliability of the electric power supply and it was raised that a system of coordination of electrical protections through appropriate fuse selectivity which will improve the reliability of medium voltage electric power supply. In order to design the coordination in electrical protection, the information must be gathered. In addition, the value of the installed fuses as well as the powers of the transformers was determined. Additionally, the nominal load of all transformers was nominated as current electrical service, which was measured during peak hours. Subsequently, the field data obtained was entered into ETAP software 12.6 and in the OETB application in Excel, in order to simulate the behavior of the different elements of the electrical system. After the simulation as well as the correct selectivity of fuses, it was determined that there are four transformers that are over dimensioned and it was redesigned the protections for a low power of service according to the needs, this change affects the selectivity significantly, otherwise; the value of the protections obtained surpass those that are actually placed. After the research study has been established an adequate selectivity of the protections and it has been determined that there are oversized transformers, which must be replaced according to the determined power..